Prospective evaluation of accuracy of fine‐needle aspiration biopsy for breast lesions using the International Academy of Cytology Yokohama System for reporting breast cytopathology. Issue 7 (23rd March 2021) - Agrawal, Shruti; Anthony, Michael Leonard; Paul, Pranoy; Singh, Divya; Mehan, Anoushika; Singh, Ashok; Joshi, Prashant Pranesh; Kumar, Arvind; Syed, Anjum; Ravi, Bina; Rao, Shalinee; Chowdhury, Nilotpal
Abstract: Background: Classification of breast lesions into different cytological groups can accurately be done using the International Academy of Cytology (IAC) Yokohama System for reporting breast cytopathology. Fine needle aspiration biopsy (FNAB) of breast lesions has been considered to be the primary investigation in detecting breast cancers, especially in low‐cost settings. The main objective of this study was to prospectively re‐confirm the diagnostic accuracy of breast FNAB using the IAC Yokohama system. Additionally, separate secondary subgroup analysis was done to confirm the accuracy of breast FNAB excluding lymph‐node positive and lymphadenopathy positive tumors. Material and methods: A prospective study was done on patients undergoing biopsy of breast lesions between September 01, 2019 and November 30, 2020 (519 biopsies on 487 unique patients). Of these 519 histopathology biopsies, 505 had corresponding FNAB report of the same site. The FNAB was reported using the IAC Yokohama system and the most suitable category was allotted in every case. The rates of malignancy for each category and the accuracy of breast FNAB in diagnosing malignancy were calculated. Results: Of the total 487 patients, 120 cases were benign on histology, while 367 were malignant. The rates of malignancy in benign, atypical, suspicious and malignant categories were 5%, 25%, 71%, and 99.7%, respectively. The diagnostic accuracy of atypical, suspicious and malignant categories was calculated as 90.1%, 95.2%, and 93.3%, respectively. Conclusion: The high diagnostic accuracy for each BIRADS category suggest excellent accuracy for Breast FNAB using the IAC Yokohama system.